Towards a Social History of Early Modern Dutch - Burke, Peter (Meertens Ethnology Cahiers, 2005)
A renowned scholar approaches the history of the Dutch language between 1500 and 1800 from a socio-cultural historian's perspective. He investigates the changing relationship between the vernacular and Latin; the incorporation (or invasion) of new words from other languages; and the movements towards standardization and purification, discussing these trends from a comparative, pan-European point of view.